A cysteine protease inhibitor GC376 displays potent antiviral activity against coxsackievirus infection - Yongkang Chen; Xiaohong Li; Min Wang; Yuan Li; Jun Fan; Jingjing Yan; Shuye Zhang; Lu Lu; Peng Zou (Current Research in Microbial Sciences, 2023)
Infection with coxsackievirus A10 (CV-A10) can cause hand-foot-mouth disease and is also associated with severe complications, including viral pneumonia, aseptic and viral meningitis. Coxsackievirus infection may also play a role in the pathogenesis of acute myocardial infarction and in the increased risk of type 1 diabetes mellitus in adults. However, there are no approved vaccines or direct antiviral agents available to prevention or treatment of coxsackievirus infection. Here, we reported that GC376 potently inhibited CV-A10 infection in different cell lines without cytotoxicity, significantly suppressed production of viral proteins, and strongly reduced the yields of infectious progeny virions. Further study indicated that GC376, as viral 3C protease inhibitor, had the potential to restrain the cleavage of the viral polyprotein into individually functional proteins, thus suppressed the replication of CV-A10. Furthermore, the drug exhibited antiviral activity against coxsackieviruses of various serotypes including CV-A6, CV-A7 and CV-A16, suggesting that GC376 is a broad-spectrum anti-coxsackievirus inhibitor and the 3C protease is a promising target for developing anti-coxsackievirus agents.